THE EFFECT OF THE PROJECT BASED LEARNING (PjBL) LEARNING MODEL ON DISCIPLINE AND COLLABORATIVE SKILLS IN BIOLOGY LEARNING OF GRADE X STUDENTS OF SMAN 2 PAMEKASAN - Yuni Maharani (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
This study aims to analyze the effect of the Project Based Learning (PjBL) learning model on the discipline and collaboration skills of 10th grade students in Biology learning at SMAN 2 Pamekasan. The background of this study is based on low learning discipline, less than optimal compliance with practicum procedures, and weak group cooperation in biology project activities. The study used a quantitative approach with a quasi-experimental design and involved two classes as samples. Data collection instruments were questionnaires, observation sheets, and project performance assessments. The results showed that PjBL had a significant influence in improving student discipline through strengthening time management, consistency in task completion, and compliance with scientific instructions. In addition, PjBL was also proven to improve collaboration skills, especially in aspects of communication, role division, conflict resolution, and group responsibility. These findings emphasize that PjBL is worthy of being recommended as an effective learning model to develop 21st-century character and skills in Biology learning.